Resolution of the Portunus gladiator species complex: taxonomic status and identity of Monomia gladiator (Fabricius, 1798) and Monomia haanii (Stimpson, 1858) (Brachyura, Decapoda, Portunidae) - Windsor, Amanda M.; Mendoza, Jose Christopher E.; Deeds, Jonathan R. (ZooKeys, 2019)
The United States Food and Drug Administration (FDA) has recently adopted DNA barcoding for the purpose of determining the species identity of commercial seafood products. This effort has revealed instances of incongruence between current scientifically accepted taxon names and those utilized by the seafood industry in product labelling. One such case is that of “ Portunushaanii ”, a name utilized by the seafood industry to label commercial products under the market name “red swimming crab.” However, carcinologists currently regard P.haanii as synonym of Portunusgladiator Fabricius, 1798, which itself is the subject of debate over whether it is a secondary homonym of Cancer gladiator Fabricius, 1793. Further complicating matters, DNA barcode sequences from commercial products match GenBank sequences identified as Portunuspseudoargentatus Stephenson, 1961. Here the complicated taxonomic history of the Portunusgladiator complex is reviewed and a resolution proposed based on combined morphological descriptions and molecular phylogenetic analyses. It is demonstrated that, given the provisions of the International Code of Zoological Nomenclature and the current elevation of Monomia Gistel, 1848, to full genus rank, its type species, Portunusgladiator Fabricius, 1798, should be treated as a valid and available taxon name. It is also shown, upon examination and comparison of types and topotypic material that Monomiahaanii (Stimpson, 1858) is a distinct taxon from M.gladiator , and Portunuspseudoargentatus Stephenson, 1961, is a junior subjective synonym of M.haanii (Stimpson, 1858). Furthermore, it is shown that crab meat sold in the US currently labeled as “ Portunushaanii ” and/or “red swimming crab” is in fact M.haanii using comparative analysis of DNA barcode sequences between museum-vouchered reference specimens, whole crabs provided directly by a seafood importer, and processed commercial products purchased at retail.